(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
For the Argentine case, studies that identify increasing implementation of three major CSR triple-impact strategies—B corporations, purpose-driven brands and marketing, and cause-related marketing—focus predominantly on supply. The present study seeks to identify consumer perceptions of these three triple-impact strategies in terms of recognition, knowledge, appreciation, and prioritization at the time of the purchase in the Argentine market. A quantitative investigation was carried out, based on a nationwide panel of 400 citizens. The results show that a majority of participants do not recognize the concepts of purpose-driven brands or the concept of B corporations. Many express difficulties in identifying such initiatives due to disinterest, ignorance, and/or lack of availability/exposure. In addition, there were non-significant differences in terms of generations, socioeconomic level, and sex. On the other hand, almost half of the panel has some familiarity with cause-related marketing campaigns, given the association with NGOs to which participating companies may donate or fund-raise. The results, particularly the limited overall recognition of these concepts, has management implications in a context of recession and spending restrictions. Video-abstract: https://youtu.be/tthIr8MSSj4